How does principal e‐leadership affect ICT transformation across different school stages in K‐12 education: Perspectives from teachers in Shanghai. (18th March 2019) - Wu, Bian; Yu, Xiaoxue; Hu, Yiling
Abstract: With the continuous deployment of ICT in K‐12 education, strong access but weak uptake has become the greatest challenge for ICT implementation in schools. As the pioneer of China's K‐12 educational reform, Shanghai draws our attention in terms of the critical factors and the underlying mechanism of ICT transformation in K‐12 schools. The study used questionnaire survey data collected from 2894 Shanghai teachers (971 primary, 990 middle and 933 high school teachers) to investigate the relationships between government ICT policy, school principal e‐leadership, ICT implementation in schools, teacher attitudes towards ICT and pedagogical change and changes in student learning. The structural equation modelling results revealed a significant influence of e‐leadership by school principals on ICT transformation in schools, confirming the critical role of e‐leadership in ICT transformation model. In addition, the higher the school stage, the more personal rather than organisational factors affected the changes in teaching and learning. The findings imply a profound sociocultural and technological dilemma due to the pressure of getting into college and risk‐taking in ICT‐related educational transformation. The study contributes to our knowledge in terms of a more nuanced ICT transformation mechanism between school stages.